A two-choice assay for noxious light avoidance with temporal distribution analysis in Drosophila melanogaster larvae - Bibi Nusreen Imambocus; Andrey Formozov; Fangmin Zhou; Peter Soba (STAR Protocols, 2022)
Summary: Two-choice assays allow assessing of different behaviors including light avoidance in Drosophila larvae. Typically, the readout is limited to a preference index at a specific end point. We provide a detailed protocol to set up light avoidance assays and map the temporal distribution of larvae based on analysis of larval intensities. We describe the assay setup and implementation of scripts for analysis, which can be easily adapted to other two-choice assays and different model organisms.For complete details on the use and execution of this protocol, please refer to Imambocus et al. (2022). : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.